2017
DOI: 10.1177/0886260517746129
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors of Child-to-Parent Violence: A Comparison Between Physical and Verbal Aggression

Abstract: Child-to-parent violence (CPV) is a social problem that remains vastly understudied compared with other forms of family violence. The aim of this study is to identify family and child risk and protective factors of CPV, and to investigate whether they differentially predict physical and verbal parent-directed violence among boys and girls. Predictors include parenting behavior during childhood (physical and verbal violence, warmth, monitoring) and respondents' individual characteristics (suicidal ideation, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
85
5
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 54 publications
12
85
5
6
Order By: Relevance
“…Nevertheless, other studies found parental acceptance and warmth to be a risk factor in aggressive children, who were not able to anticipate and understand the consequences of social behaviors and select the appropriate means to achieve their goals (Ruiz-Ortiz, Braza, Carreras, & Muñoz, 2017). On the other hand, some studies suggest that parental monitoring (e.g., setting rules and restrictions for children) is not a significant protective factor against adolescent aggression (Law, Shapka, & Olson, 2010) or significantly associated with child-to-parent violence (Beckmann, Bergmann, Fischer, & Mößle, 2017), or even that harsh parenting could exacerbate aggressiveness in adolescents (Tung & Lee, 2018). However, other studies suggest that lack of strictness and imposition may be a main risk factor related to the aggressive tendency (Furstenberg et al, 1999).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, other studies found parental acceptance and warmth to be a risk factor in aggressive children, who were not able to anticipate and understand the consequences of social behaviors and select the appropriate means to achieve their goals (Ruiz-Ortiz, Braza, Carreras, & Muñoz, 2017). On the other hand, some studies suggest that parental monitoring (e.g., setting rules and restrictions for children) is not a significant protective factor against adolescent aggression (Law, Shapka, & Olson, 2010) or significantly associated with child-to-parent violence (Beckmann, Bergmann, Fischer, & Mößle, 2017), or even that harsh parenting could exacerbate aggressiveness in adolescents (Tung & Lee, 2018). However, other studies suggest that lack of strictness and imposition may be a main risk factor related to the aggressive tendency (Furstenberg et al, 1999).…”
Section: The Present Studymentioning
confidence: 99%
“…Additionally, some gender scholars have pointed out the gap between parenting practices of warmth and strictness and their different impact on males and females, raising doubts about whether parents should act differently with their sons than with their daughters in order to prevent deviance (Bully, Jaureguizar, Bernaras, & Redondo, 2019;Carlo, Raffalli, Laible, & Meyer, 1999;Griffin, Botvin, Scheier, Diaz, & Miller, 2000;Hosokawa & Katsura, 2018). For example, parental warmth was found to be a protective factor against child-toparent violence in females but not in males (Beckmann et al, 2017), unsupervised time at home alone (low strictness) was associated with more smoking only for females (Griffin et al, 2000), and lack of parental discipline (low strictness) was related to aggression and other externalizing behavioral problems in males, but not in females (Hosokawa & Katsura, 2018).…”
Section: The Present Studymentioning
confidence: 99%
“…As Bobic (2004) points out, researchers rarely combine various levels of CPV risk factors in an integrated framework, which can potentially blur CPV understanding. There are currently exceptions, with some CPV studies combining individual and family factors (Beckmann, Bergmann, Fischer, & Mößle, 2017;Calvete, Orue, Gámez-Guadix, & Bushman, 2015) and others combing individual and social factors (Contreras & Cano, 2016;Kennedy et al, 2010;Lyons et al, 2015). However, current reviews of CPV indicate that additional research is required, given the complexity of the variables involved in the development of this type of family violence (O'Hara et al, 2017;Simmons, McEwan, Purcell, & Ogloff, 2018).…”
Section: Regardingmentioning
confidence: 99%
“…The following are available online at , Table S1: Reviewed Studies, Sample Characteristics, Methods of Assessment, and Effect Sizes. References [ 11 , 12 , 13 , 14 , 16 , 74 , 75 , 76 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] are included in the supplementary meta-analysis.…”
mentioning
confidence: 99%